Structural collapse characteristics of a 48.8 m wind turbine blade under ultimate bending loading. (December 2019) - Zhang, Lei'an; Guo, Yanzhen; Yu, Liangfeng; Wei, Xiuting; Liu, Weisheng; Huang, Xuemei
Abstract: To further study the structural failure mechanism and response characteristics of large wind turbine blades under extreme conditions, a full-scale 48.8 m blade collapse test was carried out. The strong coupling action of different damage modes are descripted by the gradual collapse process recorded by cameras. The damage behavior of suction side and pressure side, and interior and skin behavior of test blade are analysed. The test shows that the buckling of the suction side spar cap at about 21 m and cracks of the root shear web are the essential factor leading to the catastrophic failure of the entire blade, the test result is consistent with the finite element analysis. The load-deformation curve of the suction side spar cap, the deflection curves at 24 m, 36 m and tip, and the strains curves along the blade span are plotted to perform the data analysis. The critical load of 78% and deflection behavior in collapse process are determined by data analysis. The research results have great significance for improving the ultimate strength of entire blade, and provide a theoretical basis for the structural improvement of the weak points of blade. Highlights: There is a strong coupling between the crack and bulge of shear web, the spar cap buckling and the Brazier effect. The fracture of the SS spar cap at 21 m is the key factor for blade collapse by experimental test and FE analysis. The critical value of 78% test load and deflection behavior in collapse process are determined by data analysis. By the strain analysis, the strain is positively correlated with the load, but not monotonous along the blade span.